Falls prevention interventions in older adults with cognitive impairment: a systematic review of reviews - Booth, Victoria; Logan, Pip; Harwood, Rowan H.; Hood, Victoria (Mark Allen Healthcare, 2015)
Aim: This critical review explores the review material on falls prevention interventions in older adults with a cognitive impairment such as dementia.